Indonesian Language Barrier in Early Childhood Exposed to English Language Digital Media: A Case Study of Urban Families - Iskandar, Budi; Hashipah, Hani; Rahmawati, Ocha Tria; Rismayanti, Sri Ayu (Jurnal Ilmiah Profesi Pendidikan, 2025)
The rapid growth of digital media consumption among young children has increased their exposure to foreign languages, particularly English. This phenomenon raises concerns about its potential impact on the development of their native language, Indonesian language. The purpose of this study is to identify the obstacles to Indonesian language experienced by children and to understand the effect of English-language digital media on their language development. This study examines the effect of exposure to English-language digital media on Indonesian language skills in early childhood. The phenomenon found shows that 5-year-old children who are more often exposed to digital content in English have difficulty in using Indonesian, especially in choosing words, constructing sentences, and communicating with peers. This study employed a qualitative case study methodology, with data collected through structured interviews with parents, systematic observations of children's communicative behaviors, and comprehensive documentation of their daily language usage. The results of the study show that intensive exposure to digital media and family communication patterns play a major role in children's language development. Children tend to be more accustomed to using English and have difficulty communicating in Indonesian. This study concludes that early exposure to English can affect children's Indonesian language skills. The recommendation given to parents is to reduce exposure to English-language digital media and increase interaction in Indonesian.